Cutaneous tuberculosis—ambiguous transmission, bacterial diversity with biofilm formation in humoral abnormality: case report illustration - Zdziarski, Przemysław; Paściak, Mariola; Chudzik, Anna; Kozińska, Monika; Augustynowicz-Kopeć, Ewa; Gamian, Andrzej (Frontiers in Public Health, 2023)
Background Cutaneous tuberculosis (CTB) and its paucibacillary forms are rare and difficult to diagnose, especially in immunocompromised patients with significant comorbidity. The aim of the study was to introduce the modern concept of the microbiome and diagnostic chain into clinical practice (patient-centered care) with the presentation of an atypical form of cutaneous tuberculosis with necrotizing non-healing ulcers leading to polymicrobial infection. Methods The study material included samples from sputum, broncho-alveolar lavage and skin ulcer, taken from a patient developing cutaneous tuberculosis. The microbiological investigation was performed, and identification of the isolates was carried out using genotyping and the matrix-assisted laser desorption ionization-time of flight mass spectrometry. Results The immunocompromised patient with humoral abnormality (plasma cell dyscrasia) and severe paraproteinemia developed multiorgan tuberculosis. Although cutaneous manifestation preceded systemic and pulmonary symptoms (approximately half a year), the mycobacterial genotyping confirmed the same MTB strain existence in skin ulcers and the respiratory system. Therefore, the infectious chain: transmission, the portal of entry, and bacterial spreading in vivo, were unclear. Microbial diversity found in wound microbiota (among others Gordonia bronchialis, Corynebacterium tuberculostearicum, Staphylococcus haemolyticus, and Pseudomonas oryzihabitans) was associated with the spread of a skin lesion. The in vitro biofilm-forming capacity of strains isolated from the wound may represent the potential virulence of these strains. Thus, the role of polymicrobial biofilm may be crucial in ulcer formation and CTB manifestation. Conclusions Severe wound healing as a unique biofilm-forming niche should be tested for Mycobacterium (on species and strain levels) and coexisting microorganisms using a wide range of microbiological techniques. In immunodeficient patients with non-typical CTB presentation, the chain of transmission and MTB spread is still an open issue for further research.